A high percentage of hospital‐acquired neonatal bacteraemia but rare resistance to standard antibiotic regimens. (24th February 2022) - Dabaja‐Younis, Halima; Atrash‐Nimri, Nili; Diab, Shaden; Jubran, Huda; Geffen, Yuval; Kassis, Imad
Abstract: Aim: We examined community and hospital‐acquired bacteraemia, namely bloodstream infections or meningitis, and looked at the clinical features and outcomes of cases. Methods: The study comprised infants under 3 months of age, who were admitted to a tertiary referral centre in northern Israel with bacteraemia from 2010–2019. Causative pathogens, antibiotic susceptibility and mortality were retrospectively recorded. Results: We identified 314 infants, 325 episodes of bacteraemia and 344 pathogens. Meningitis was identified in 22 (7.0%) infants. Hospital‐acquired bacteraemia accounted for 84.8% of the 325 episodes. Coagulase‐negative staphylococci (33.9%) was the most prevalent pathogen in the hospital‐acquired cases, while Escherichia coli (37.2%) dominated the community‐acquired cases. The susceptibility of Gram‐negative early‐onset sepsis cases to ampicillin–gentamicin or ampicillin–cefotaxime was 96% and 94.7% for hospital‐acquired cases and 91.7% and 88% for community‐acquired cases, respectively. Susceptibility to piperacillin–tazobactam or amikacin in late‐onset sepsis were 92.8% and 98%, respectively, in hospital‐acquired cases. The 30‐day mortality was 5.7% in infants with hospital‐acquired cases. Risk factors were Arab ethnicity ( p < 0.028), haemodynamic instability (<0.001) and Gram‐negative sepsis (0.043). Conclusion: Most cases of bacteraemia were acquired during hospitalisation and these accounted for the majority of the deaths. Resistance to standard antibiotic regimens was rare.